Kajian Pemikiran Pendidikan Islam Abdurrahman An-Nahlawi Dalam Kerangka Pendidikan Modern: DOI 10.58569/jies.v2i2.978 - Sukarman (Pascasarjana Universitas Islam Jakarta, 2024)
This study aims to explore the idea of education promoted by one of the great figures in Islamic education, namely Abdurrahman An-Nahlawi. This great figure of Islamic Education has inspired one of the education leaders in Indonesia, namely Ki Hajar Dewantara. These educational ideas include goals, educational concepts, basics, vision, mission, goals, methods, media, to the principles of Islamic education. This research is a conceptual literature review with a qualitative descriptive approach. The findings of this study are that Abdurrahman An-Nahlawi has laid the foundations of a very comprehensive education that is widely embraced by educational leaders and is still relevant today. The concept of At-tarbiyah is concrete proof of the fruit of his thoughts